Perturbed Motions of a Rotating Symmetric Gyrostat - Ismail, A.I.; Amer, T.S.; Shaker, M.O. (Engineering Transactions, 1998)
The aim of the present paper is to provide analytical solutions for the perturbed problem of the behaviour of a symmetric gyrostat about a fixed point. This gyrostat is acted upon by a gyrostatic momentum $l_s (s = 1, 2, 3)$, variable restoring moment $k$ and perturbing moments $M_i (i = 1, 2, 3)$. The moment $k$ is introduced in view of the rotation of gyrostat under the action of electro-magnetic field. The solutions are achieved when the third component of the gyrostatic momentum is different from zero $(l_3 eq 0)$. The averaging method is applied to investigate the first order approximate solutions of resonant and non-resonant cases.